DEVELOPMENT OF THE “I EXIST, I AM VALUABLE” E-BOOKLET MEDIA FOR PREVENTING SELF-INJURY BEHAVIOR AT SMPN 5 MAKASSAR - Rovida Nurhusna Abinsair; Farida Aryani; Abdullah Pandang (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to develop and examine the practicality of the e-booklet “Aku Ada, Aku Berharga” (“I Exist, I Am Valuable”) as an educational and preventive medium to reduce self-injury behavior among students of SMP Negeri 5 Makassar. The rise in self-injury among adolescents is associated with difficulties in managing stress, social pressure, and low self-worth. Therefore, there is a need for educational, contextual, and easily accessible informational media for students. This research employed a modified Borg & Gall development model consisting of seven stages: preliminary study, initial design planning, prototype development, expert validation, product revision, limited trial, and final refinement. Data were collected through student needs questionnaires, expert validation sheets for content and media, and practicality assessments conducted by Guidance and Counseling (BK) teachers and students. The results indicate that the e-booklet achieved a “very valid” rating in terms of content, appearance, and language, and was categorized as “very practical” based on user evaluations. The e-booklet was perceived as engaging, communicative, and aligned with adolescents’ psychosocial needs. Thus, the “Aku Ada, Aku Berharga” e-booklet is feasible to be used as a preventive counseling medium to enhance students’ understanding, emotional regulation, and self-worth in efforts to prevent self-injury behavior.